2007
DOI: 10.1089/thy.2006.0209
|View full text |Cite
|
Sign up to set email alerts
|

Smaller Thyroid Gland Volume with High Urinary Iodine Excretion in Japanese Schoolchildren: Normative Reference Values in an Iodine-Sufficient Area and Comparison with the WHO/ICCIDD Reference

Abstract: Iodine deficiency disorders (IDDs) are serious global public health problems and approximately 2 billion people are at risk of IDD complications. Urine iodine and thyroid size by ultrasound in school-age children are important indicators for assessing IDD in a population. Interpretation of sonographically measured thyroid volume requires valid reference criteria from iodine-sufficient populations, and in 2003 WHO (World Health Organization)/ICCIDD (International Council for the Control of Iodine Deficiency Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
40
3
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 29 publications
11
40
3
9
Order By: Relevance
“…However, national survey data for iodine intake is not currently available because iodine is not included as a target nutrient in the national health and nutrition survey. According to our collaborative studies with WHO in Tokyo and Hokkaido, the median UI value in schoolaged children is 281 to 288ÎŒg/L, suggesting a sufficient iodine status with more than adequate iodine intake [35][36][37]. In addition, children with a high UI excretion and increased thyroid gland volume were observed in a coastal area of Hokkaido [37].…”
Section: Relationship Between Maternal Tsh Ft 4 Uic and Neonatal Tshmentioning
confidence: 91%
“…However, national survey data for iodine intake is not currently available because iodine is not included as a target nutrient in the national health and nutrition survey. According to our collaborative studies with WHO in Tokyo and Hokkaido, the median UI value in schoolaged children is 281 to 288ÎŒg/L, suggesting a sufficient iodine status with more than adequate iodine intake [35][36][37]. In addition, children with a high UI excretion and increased thyroid gland volume were observed in a coastal area of Hokkaido [37].…”
Section: Relationship Between Maternal Tsh Ft 4 Uic and Neonatal Tshmentioning
confidence: 91%
“…After publishing these data, recent studies on thyroid volume confirmed the international reference values although the number of cases are small (approximately 200-5000 cases) in all studies [11][12][13][14][15][16]. In Japan, Fuse et al compared the international reference values for Japanese and thyroid volumes of approximately 1000 schoolchildren [11]. They con- NA denotes the data was not applicable.…”
Section: Discussionmentioning
confidence: 95%
“…Zava and Zava 7 estimated that Japanese iodine intake, which comes largely from seaweed consumption, ranges from 1 to 3 mg/day. The mean or median UIC of Japanese residents ranges from 281 to 3300 Όg/L in many regions of Japan 8, 9, 10, 11, 12, 13, 14.…”
Section: Introductionmentioning
confidence: 99%